The relationship between serum and urinary iodine levels and thyroid hormones in patients with goitre living in Malatya region - Akinci, Aysehan; Balat, Ayse; Turgut, Mehmet; Cekmen Dr Hasan Kucukbay Zehra Kucukbay, Mustafa; Yologlu, Saim; Gozukara, Engin (Annals of Medical Research, 2021)
None